ANALYSIS OF THE APPLICATION OF SPECIAL INVESTIGATION TECHNIQUES: COVERT, SPECIAL, REVEALING AND VIRTUAL AGENTS IN THE FIGHT AGAINST ORGANIZED CRIME: REGARDING LEGISLATIVE DECREE 1611 WHICH MODIFIED ARTICLE 341 OF THE PERUVIAN CRIMINAL PROCEDURE CODE - Aguinaga Vidarte, Aguinaga Vidarte (2024)
The object of study of this work focuses on Legislative Decree 1611 that modified article 341 of the Criminal Procedure Code, which established, among others, the incorporation of new special investigation techniques. This work will address the purpose of special investigation techniques in clarifying criminal acts carried out by criminal organizations, as well as the principles that regulate them and prevent their application from violating fundamental rights of the procedural parties. On the other hand, the application of special investigation techniques will be described, such as: covert, revealed, special and virtual agents; This is due to the publication of Legislative Decree 1611, which modified article 341 of the Criminal Procedure Code. Finally, the importance of the content of said modification in the fight against organized crime will be detailed.